Zinc finger E-Box binding homeobox 2 (ZEB2)-induced astrogliosis protected neuron from pyroptosis in cerebral ischemia and reperfusion injury. Issue 2 (20th December 2021) - Zhao, Zhixin; Hu, Xiaoming; Wang, Jie; Wang, Jianfeng; Hou, Yong; Chen, Suyun
ABSTRACT: Ischemia injury can cause cell death or impairment of neuron and astrocytes, and thus induce loss of nerve function. central nervous systems injury induces an aberrant activation of astrocytes called astrogliosis. Pyroptosis, which is a kind of programmed cell death, was proved play an important role in ischemia injury. Zinc Finger E-Box Binding Homeobox 2 (ZEB2) promoted neuron astrogliosis, which play a protected role in neuron regeneration. However, its precise mechanism remains unclear. This study investigated the mechanism of ZEB2 on astrogliosis and neuron regeneration after cerebral ischemia reperfusion condition. To confirm our hypothesis, Neurons and astrocytes were isolated from fetal Sprague Dawley rats, in vivo Middle Cerebral Artery Occlusion/reperfusion (MCAO/R) rat model and in vitro oxygen-glucose deprivation/reperfusion (OGD/R)-treated astrocytes and neurocytes model were constructed. Our results showed that ZEB2 was expressed in nucleus of astrocyte and upregulated after OGD/R induction, ZEB2 promoted astrogliosis. Further upregulation of ZEB2 promoted the astrogliosis, which promoted neuron proliferation and regeneration by decreased pyroptosis. Moreover, this finding was further confirmed in vivo MCAO/R rat model. Overexpression of ZEB2 promoted astrogliosis, which decreased infarct volume and accumulated recovery of neurological function by alleviated pyroptosis. This finding revealed that ZEB2 was a regulator of the astrogliosis after ischemia/reperfusion injury, and then astrogliosis promoted neuron regeneration via decreased neuron pyroptosis. Therefore, ZEB2 may be a potential therapeutic target for ischemia/reperfusion injury.